SiAlON bonded SiC ceramics from silicone polymer and nanosized fillers. (1st April 2013) - Bernardo, E; Parcianello, G; Colombo, P; Hess, U; Treccani, L; Rezwan, K
<x xml:space="preserve">Abstract</x> Abstract The development of β′-SiAlON from silicone resins, mixed with oxide nanoparticles, has already been shown to be particularly complex due to the phase separation of the oxycarbide ceramic residue of the polymers and to the formation of oxygen rich intermediate phases. This paper focuses on the fabrication of SiAlON-SiC composites, in which the phase separation is exploited in yielding part of SiC together with a reactive mixture of silica and carbon, to be combined with a relatively low amount of alumina nanoparticles and additional carbon, from carbon black or phenolic resin. SiC particles were bound by a polymer derived β′-SiAlON phase after treatment at 1500°C (3 h) in nitrogen; although featuring a significant amount of residual porosity (>44%), the developed ceramic composites have remarkable mechanical properties (biaxial bending strength exceeding 70 MPa), especially when containing Y2O3 doping (3 wt-%).